Francis Storr correspondence - Storr, Francis, 1839-1919.
Letters received by Storr from Robert Browning (1881 February 13), Charles Darwin (1875 March 5), and William Hale White (1909 February 16), and letter (1907 December 24) from White to Storr's wife, Rose Lloyd Storr.
Negative photocopies.
British educator and editor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Browning, Robert, -- 1812-1889 -- Correspondence; Darwin, Charles, -- 1809-1882 -- Correspondence; Storr, Rose Lloyd -- Correspondence; White, William Hale, -- 1831-1913 -- Correspondence; Editors; Educators